Human peripheral and gastric lymphocyte responses to Helicobacter pylori NapA and AphC differ in infected and uninfected individuals. Issue 1 (10th December 2004) - Windle, H J; Ang, Y S; Morales, V A; McManus, R; Kelleher, D
Abstract : Background: In this study, we identify the nature of the immunological response of human peripheral blood mononuclear cells (PBMC) and lamina propria gastric lymphocytes (LPL) to two Helicobacter pylori antigens, the neutrophil activating protein (NapA) and alkyl hydroperoxide reductase (AphC). These antigens were identified and selected for study based on the observation that serological recognition of these proteins was associated with H pylori negative status in humans. Aims: The aim was to study the serological, proliferative, and cytokine responses of PBMC and LPL, obtained from H pylori infected and uninfected individuals, to these antigens. Methods: Patient serum, PBMC, and LPL were used to determine antibody isotype, and proliferative and cytokine responses to recombinant forms of NapA and AphC using western blotting and ELISA. Results: Western blotting revealed antibody reactivity to recombinant NapA and AphC among the H pylori negative population studied. Both the proliferative and interferon γ responses of PBMC and LPL to NapA and AphC were significantly higher in H pylori negative compared with H pylori positive subjects. Analysis of the IgG subclass profiles to both antigens revealed a T helper 1 associated IgG3 antibody response in uninfected individuals. However, interleukin 10 production was greater in H pylori positive individuals in response to these antigens. Conclusions: Taken together these data are consistent with an immune response to these antigens skewed towards a T helper 1 response in the uninfected cohort.